Terrestrial plant methane production and emission - Bruhn, Dan; Møller, Ian M; Mikkelsen, Teis N; Ambus, Per (Physiologia plantarum, 2012)
In this minireview, we evaluate all experimental work published on the phenomenon of aerobic methane (CH4) generation in terrestrial plants and plant. Clearly, despite much uncertainty and skepticism, we conclude that the phenomenon is true. Four stimulating factors have been observed to induce aerobic plant CH4 production, i.e. cutting injuries, increasing temperature, ultraviolet radiation and reactive oxygen species. Further, we analyze rates of measured emission of aerobically produced CH4 in pectin and in plant tissues from different studies and argue that pectin is very far from the sole contributing precursor. In consequence, scaling up of aerobic CH4 emission needs to take into consideration other potential sources than pectin. Due to the large uncertainties related to effects of stimulating factors, genotypic responses and type of precursors, we conclude that current attempts for upscaling aerobic CH4 into a global budget is inadequate. Thus it is too early to draw the line under the aerobic methane emission in plants. Future work is needed for establishing the relative contribution of several proven potential CH4 precursors in plant material.